Analysis of Cultural Preservation Policy in Depok Regency Youth and Sports Tourism Culture Office - Rio Rinaldy (Journal of Business Social and Technology, 2021)
The Research Title is An Analysis of Cultural Preservation Policy at the Depok Regency Youth and Sports Tourism Cultural Office. This is because aside from the culture and the community, the role of the Government, namely the Department of Youth Tourism culture and sports Depok regency is very large role in the preservation of culture, especially Tayub Dance. This research is about the analysis of cultural preservation policies in the Depok Regency Youth and Sports Tourism Cultural Office on tayub dance arts in Mertasinga Village, Gunung Jati SubDistrict which aims to 1) To find out the implementation of the cultural preservation program policy of the Department of Culture, Tourism, Youth and Sports Depok regency; 2) To find out the factors that support the policy in the cultural conservation program of the Depok Regency Department of Culture, Tourism, Youth and Sports; 3) To find out the obstacles faced in the cultural preservation policy in the Department of Culture, Tourism, Youth and Sports Depok Regency. This research uses qualitative descriptive research that describes the analysis of cultural preservation policies in the Department of Cultural Tourism of Youth and Sports, and also uses interview methods for data search. The results of this study show that 1) There is still no implementation of cultural preservation program policy in the Department of Culture, Tourism, Youth and Sports Depok Regency, 2) There are still not maximal cultural development in the Department of Culture, Tourism, Youth and Sports Depok Regency, 3) There are obstacles to cultural preservation policy in the Department of Culture, Tourism, Youth and Sports Depok Regency.